Meat consumption, health and the environment - Godfray, C; Aveyard, P; Garnett, T; Hall, J; Key, T; Lorimer, J; Pierrehumbert, R; Scarborough, P; Springmann, M; Jebb, S (American Association for the Advancement of Science, 2018)
Both the global average per capita consumption of meat and the total amount of meat consumed are rising, driven by increasing average individual incomes and by population growth. The consumption of different types of meat and meat products has substantial effects on people’s health, and livestock production can have major negative effects on the environment. Here, we explore the evidence base for these assertions and the options policy-makers have should they wish to intervene to affect population meat consumption. We highlight where more research is required and the great importance of integrating insights from the natural and social sciences.